Intervensi Kelompok untuk Meningkatkan Self Transcendence pada Pasien dengan Penyakit Kronis: Scoping Review - Niken Wulan Hasthi Murti; Suci Nurjanah; Sari Artauli Lumban Toruan (NHM PRESS, 2023)
The role of nurses is urgently needed in patients with long-term treatment, to optimize the patient's ability and maintain self-transcendence. Self-transcendence is an individual's ability to gain meaning in themselves and align and accept the current situation. This scoping review aimsed to analyze the effectiveness of group therapeutic interventions that can improve self-transcendence in patients with chronic diseases. This was a scoping review through a review of articles on group therapeutic interventions that have been used to improve self-transcendence in patients with chronic diseases. Search articles accessed through three databases including ScienceDirect, Pub-Med and ProQuest, with a search year span of 2011 and 2020. This scoping reviews was carried out through 5 processes, that consist of: a) identifying research questions, b) identifying relevant types of research, c) selecting the type of research, d) mapping the data, and e) summarizing and reporting the data. The results of this study show that group therapy has a meaningful influence on improving self-transcendence in patients with chronic diseases. Group therapy interventions can be given recommended as nursing self-interventions to improve the self transcendence of patients with chronic diseases.